Flebotomíneos (Diptera, Psychodidae) de área de cerrado no Município de Corumbataí, Centro-leste do Estado de São Paulo, Brasil. - Cutolo, André A. [UNESP]; Von Zuben, Claudio J. [UNESP] (FapUNIFESP (SciELO), 2008)
Distribution and ecology knowledge of sandfly species is essential for epidemiology vigilance and risk determination for transmission of leishmaniasis. Sandfly trapping was carried out in a cerrado strictu sensu vegetation fragment in a rural area of Corumbataí Municipality, São Paulo State, Brazil, during July to November 2004. Two CDC light traps were used from 18h to 8h, once a month, resulting in 112 total hours of capture. During this period, 60 sandfly specimens of ten different species were sampled. The most abundant species and the one found in all captures was Pintomyia monticola totalizing 15 (25.0%) specimens, the second more abundant one was P. pessoai with 14 (23.3%) and the third one was Brumptomyia guimaraesi with 12 (20.0%) individuals collected. Other captured species were Psathyromyia aragaoi, B. avellari, B. brumpti, B. cunhai, P. bianchigalatiae, Evandromyia termitophila and Nyssomyia whitmani which corresponded to 19 (31.2%) specimens captured. Pintomyia pessoai and N. whitmani presence indicates transmission risk of American Cutaneous Leishmaniasis in the area.
Sandflies (Diptera: Psychodidae) from a cerrado area of Corumbataí Municipality, Central East Region of São Paulo State, Brazil
Keywords: animal; Brazil; population density; Psychodidae; Animals; Population Density